2019
DOI: 10.21873/invivo.11485
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid Induces Apoptotic Cell Death Through AIF and Endo G Release Through a Mitochondria-dependent Pathway in NCI-H292 Human Lung Cancer Cells In Vitro

Abstract: Background/Aim: Ursolic acid (UA), a triterpene compound present in natural plants, has been shown to induce cytotoxic effects on many human cancer cells through induction of cell-cycle arrest and apoptosis. This study investigated the effects of UA on human lung cancer NCI-H292 cells in vitro. Materials and Methods: Flow cytometric assay was used to measure the percentage of cell viability, apoptotic cell death by double staining of annexin V and propidium iodide (PI), production of reactive oxygen species (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 44 publications
(32 reference statements)
0
28
0
Order By: Relevance
“…Ursolic acid has been reported to inhibit the in ammatory factors TNF-α and IL6, LOX-1, VCAM-1, ICAM, IL5, IL13 and IL17 [30]. Another study shows that ursolic acid increases apoptosis in lung cancer cells [31]. In addition, it is also reported that UA via decreasing Bcl-2, Mcl-1, TCTP expression and increasing apoptotic proteins such as TNF-α, Fas, FADD and BAX results in activation of caspase-3 and PARP which induces apoptosis of the liver cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…Ursolic acid has been reported to inhibit the in ammatory factors TNF-α and IL6, LOX-1, VCAM-1, ICAM, IL5, IL13 and IL17 [30]. Another study shows that ursolic acid increases apoptosis in lung cancer cells [31]. In addition, it is also reported that UA via decreasing Bcl-2, Mcl-1, TCTP expression and increasing apoptotic proteins such as TNF-α, Fas, FADD and BAX results in activation of caspase-3 and PARP which induces apoptosis of the liver cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…1A. The MTT assay suggested that ursolic acid inhibited the proliferation of HOS cells in a concentration-dependent manner; through the calculation method of predecessors (14), the IC 50 of ursolic acid was ~35 µmol/l ( Fig. 1B and C).…”
Section: Ursolic Acid Inhibits the Growth And Invasion Of Hos Cellsmentioning
confidence: 92%
“…7,8 Several studies have confirmed that UA has shown strong anticancer effects against lung cancer, BC, and so on. 9,10 Yeh et al investigated that UA inhibited cancer cell invasion, migration, and proliferation in MDA-MB-231 via down-regulating u-PA and MMP-2 expression, and upregulating the expression of PAI-I and TIMP-2. 11 UA has also been reported to reduce the phosphorylation of AKT/ mTOR signaling for modulating proliferation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%